Malaysian higher education students’ perceptions on teaching, learning, assessments, and peer interaction during the transition from open distance learning to hybrid and blended learning - Mohd Yusof, Fairuz Husna; Satimin, Onaliza; Saidin, Azidatun-Noor; Obaid, Awatif; Othman, Mohammad Ariff; Sulaiman, Normala; (Kasbon), Hanisah Bon (Journal of Islamic, Social, Economics and Development, 2025)
The COVID-19 pandemic has significantly impacted various aspects of our lives, including education. Teaching and learning methods have evolved as institutions adopted alternative approaches to meet educational demands during the crisis. This shift is particularly evident in higher education institutions (HEIs). As schools continue to have face-to-face classes as prior to COVID, many HEIs in Malaysia transitioned from using open distance learning (ODL) to hybrid and blended learning. This somehow has brought up various responses from the students in many aspects. Thus, this study aims to explore students’ perceptions towards teaching and learning, assessments and interactions with peers based on their experiences learning through ODL, hybrid learning and blended learning. To collect the data, a survey was conducted among public and private HEIs in Malaysia using a structured questionnaire. The survey recorded responses from 202 respondents which were selected based on random sampling. The findings highlight that there was a range of students’ reactions and there is a need for hybrid learning designs that balance flexibility with structured instructional support to maintain engagement, uphold academic integrity, and foster consistent collaboration. Although many students value the flexibility offered by hybrid and blended learning, there are concerns on quality and fairness of assessments and the level of interaction among peers. This study benefits the lecturers and HEI management in managing overall learning experiences by addressing the concerns of the stakeholders for better teaching and learning approach in the future.